2017
DOI: 10.1016/j.tranon.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Sarcomatoid Carcinoma with ALK Rearrangement: Frequency, Clinical-Pathologic Characteristics, and Response to ALK Inhibitor

Abstract: PURPOSE: The incidence of anaplastic lymphoma kinase (ALK) rearrangement in pulmonary sarcomatoid carcinoma (PSC) is controversial. In this study, we aimed to reveal the reliable frequency and the clinical-pathologic characteristics of pulmonary sarcomatoid carcinoma (PSC) with ALK rearrangement in Chinese population, and to provide insight into the translatability of anti-ALK treatment in this treatment-refractory disease. METHODS: Immunohistochemistry (IHC) using a Ventana anti-ALK (D5F3) rabbit monoclonal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…[12][13][14] These findings suggest that ALK-positive PPC patients may be older than patients with ALK-positive lung adenocarinoma. 10 Moreover, it is notable that the epithelial components of our patients and those of the three aforementioned patients were all adenocarcinomas, consistent with the findings of Chen et al 15 that 4 of 5 ALK-positive patients with PSC had adenocarcinomas with epithelial components. These results indicate that ALK rearrangements in patients with PPC may likely arise in those with an adenocarcinoma epithelial component.…”
Section: Discussionsupporting
confidence: 91%
“…[12][13][14] These findings suggest that ALK-positive PPC patients may be older than patients with ALK-positive lung adenocarinoma. 10 Moreover, it is notable that the epithelial components of our patients and those of the three aforementioned patients were all adenocarcinomas, consistent with the findings of Chen et al 15 that 4 of 5 ALK-positive patients with PSC had adenocarcinomas with epithelial components. These results indicate that ALK rearrangements in patients with PPC may likely arise in those with an adenocarcinoma epithelial component.…”
Section: Discussionsupporting
confidence: 91%
“…20,21,27 To date, targeting of oncogenic KRAS has not been successful. Other targetable mutations, such as ALK translocations, are rare but encountered, 28,29 as are BRAF V600E mutations. 2 ALK and MET amplifications are also seen.…”
Section: Targeted Therapymentioning
confidence: 99%
“…There is no experience of success or guideline for treatment of such disorders in clinical practice. Referring to the commonly used treatment for NSCLC, the patient should be treated with crizotinib because of positive EML4- ALK fusion 19. However, NSCLC may fail to respond to molecular targeted therapy because of adverse TP53 and KRAS mutations 13.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced PSC always has a very poor prognosis and responds poorly to conventional platinum-based chemotherapy 14,20. It has been reported that ALK inhibitors may be an effective treatment for ALK rearrangement in PSC 19. However, KRAS mutations can result in a detrimental impact on prognosis and responsiveness to platinum-based chemotherapy in NSCLC18,21 as well as in PSC 1416.…”
Section: Discussionmentioning
confidence: 99%